Optimization of cholesterol oxidase production and 16S rRNA partial sequence of Bacillus cereus strain KAVK4 isolated from butter - Amutha Kuppusamy, Kokila Vasantha Kumar (Journal of Applied Pharmaceutical Science, 2016)
The aim of the present research work was to optimize cholesterol oxidase production and partial sequencing of 16S rRNA gene region of Bacillus cereus strain KAVK4 by PCR. Bacillus cereus is a gram positive bacterium isolated from butter, Tamil Nadu, India and was cultured in a nutrient medium containing cholesterol at 37°C for 24 hours. Partial sequence of 16S rRNA gene was amplified by PCR and sequenced, the sequence data was submitted to NCBI. The production of cholesterol oxidase of Bacillus cereus strain KAVK4 was analyzed by qualitative methods such as Colony staining method & Cholesterol Oxidase indicator plate method and quantitative method. The maximum production of cholesterol oxidase was checked in media with different carbon source, nitrogen source, and metal ions source. The different physical parameters like pH, temperature and time were checked. Bacillus cereus strain KAVK4 partial sequence of 16S rRNA gene region resulted 1366bp. The sequence data was submitted to NCBI and the accession number is KP792775. Bacillus cereus strain KAVK4 was optimized at media containing Fructose, Beef Extract, Ammonium Nitrate and Magnesium sulphate at pH 7.5 at Room temperature and incubation period was about 32 hrs. Bacillus cereus strain KAVK4 was found to produce maximum level of cholesterol oxidase (1.67 U/ml). The result obtained in this work was clearly indicated that Bacillus cereus strain KAVK4 was capable of producing maximum level of cholesterol oxidase at pH 7.5 and incubation was 32 hrs.
Keywords: Bacillus cereus strain KAVK4, Sequencing, 16S rRNA gene, Cholesterol oxidase, Optimization.